1985
DOI: 10.3177/jnsv.31.225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary taurine on cholesterol gallstone formation and tissue cholesterol contents in mice.

Abstract: SummaryThe inhibitory effect of dietary taurine on cholesterol gallstone formation was studied using male mice of Jcl: ICR strain. Mice were provided three kinds of semi-purified diet; a cholesterol-free diet (standard), a lithogenic diet containing 0.5% cholesterol and 0.25% sodium cholate (C-CA), and a lithogenic diet supplemented with 5% taurine. The changes of total cholesterol in serum, cholesterol mass in the liver and the gall bladder, and gallstone incidence were studied as a function of time. Gallston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
0
10
1
Order By: Relevance
“…Addition of taurine with cholesterol feeding augmented both serum cholesterol and L.I, in bile significantly in this study. The present findings are interesting and contrary to those of the previous reports (Yamanaka et al 1985;Uenoyama et al 1985). In man, the rate of cholesterol absorption is low in contrast to other species (Turley and Dietschy 1982).…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Addition of taurine with cholesterol feeding augmented both serum cholesterol and L.I, in bile significantly in this study. The present findings are interesting and contrary to those of the previous reports (Yamanaka et al 1985;Uenoyama et al 1985). In man, the rate of cholesterol absorption is low in contrast to other species (Turley and Dietschy 1982).…”
Section: Discussioncontrasting
confidence: 57%
“…Our results are similar to those of Hardison and Grundy (1983). In rats and mice, it has been reported that taurine has a hypocholesterolemic effect (Tsuji et al 1979;Yamanaka et al 1985) owing to activation of cholesterol 7a-hydroxylase and successive augmentation of bile acid synthesis. Bile acids are exclusively conjugated with taurine in rats and mice, in contrast to man and rabbit where bile acids conjugate mainly with glycine (Truswell et al 1965).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of diet in the pathogenesis of GS has been much debated. Information on this issue can be obtained from experimental, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] clinical, [19][20][21][22][23][24][25][26] and epidemiological studies. [27][28][29][30][31][32][33][34][35] These latter studies have mainly investigated symptomatic GS subjects who were aware of having GS or subjects who had been previously submitted to cholecystectomy.…”
mentioning
confidence: 99%
“…We previously reported on the decrease in the incidence of gallstone formation and hepatic cholesterol mass (2,3) and the increase in fecal bile acid excretion (4) effected by dietary taurine in hypercholesterolemic mice. These results suggested that the protective effect of dietary taurine against cholesterol gallstone formation is related to the stimulation of bile acid synthesis (4).…”
mentioning
confidence: 99%